Savor the moment [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. Bride quartet, 2010)
Wedding baker Laurel McBane is surrounded by romance working at Vows wedding planning company with her best friends Parker, Emma, and Mac. But she's too low-key to appreciate all the luxuries their clients seem to long for. What she does appreciate is a strong, intelligent man, a man just like Parker's older brother Delaney, on whom she's had a mega-crush since childhood.